1999
DOI: 10.1095/biolreprod61.5.1235
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Kallikrein Gene Expression and Enzymatic Activity in Porcine Endometrium During the Estrous Cycle and Early Pregnancy1

Abstract: Porcine conceptuses rapidly elongate within the uterine horns prior to the period of placental attachment. During the time of elongation, secretion of estrogen by the developing conceptuses occurs for the establishment of pregnancy through maintenance of corpora lutea and facilitation of placental attachment. Factors associated with the uterine luminal epithelium accentuate embryo attachment by allowing close contact between the conceptus and the uterine epithelium. Kallikrein, a serine protease, may be involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
(41 reference statements)
3
19
0
Order By: Relevance
“…Kallikrein has been discussed to be one likely candidate (Denker and Fritz 1979). Recently it has been shown that kallikrein is expressed in the endometrium as well as in the embryo during early pregnancy in the pig and mouse (Chan et al 1999;Vonnahme et al 1999). The second major protein of embryonic origin detected in this study is a 50-kDa protein pI 6.0, already detectable at day 5 (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Kallikrein has been discussed to be one likely candidate (Denker and Fritz 1979). Recently it has been shown that kallikrein is expressed in the endometrium as well as in the embryo during early pregnancy in the pig and mouse (Chan et al 1999;Vonnahme et al 1999). The second major protein of embryonic origin detected in this study is a 50-kDa protein pI 6.0, already detectable at day 5 (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Both IαIH4 protein expression and kallikrein enzymatic activity increase within the uterine environment during the peri-implantation period of pigs (Geisert et al 1998 ;Vonnahme et al 1999 ). The IαIH4 can directly engage the αvβ3 integrin receptor, as well as interact with hyaluronic acid within the ECM to aid in the initial stages of implantation.…”
Section: Trophoblast Attachment and Adhesionmentioning
confidence: 99%
“…Geisert and coworkers [1998] have reported the detection of a 120-kD multi-functional inter-·-trypsin inhibitor heavy chain-like (I·IH4) protein during the mid-luteal phase of the estrous cycle and during the period of Tr attachment to the uterine epithelium. This protein complex may be part of the kallikrein-kininogen-kinin system [Geisert and Yellich, 1997] which serves as a substrate for the plasma serine protease kallikrein; the activity of this enzyme increases in the uterine lumen on Day 12 of pregnancy [Vonnahme et al, 1999]. The I·IH4 has the ability to interact with extracellular matrix component hyaluronic acid and may aid in the ini- tial stages of attachment.…”
Section: Other Potential Integrin-receptor Ligands Present In Histotrophmentioning
confidence: 99%
“…Prothrombin and thrombin are secreted by the rat uterus [Henrikson et al, 1994]. Rat uterine kallikrein activity is stimulated by estrogen and intralumenal stimulation, and has been implicated in implantation and decidualization [Corthorn and Valdes, 1994;Valdes et al, 1993Valdes et al, , 1996Corthorn et al, 1997], whereas kallikrein activity is present in uterine flushings of cyclic pigs during a period that corresponds to conceptus elongation [Vonnahme et al, 1999]. Likewise, cathepsin-L proteolytic activity and protein has been detected in endometrial GE and uterine flushings from early implanting pigs .…”
Section: Potential Integrin/matrix-activating Components Of Histotrophmentioning
confidence: 99%